A review of the Japanese species of Barycnemis Förster (Hymenoptera: Ichneumonidae: Tersilochinae) - Khalaim, Andrey I. (Zootaxa, 2015)
Four species of the genus Barycnemis Förster are found to occur in Japan: B. dissimilis (Gravenhorst), B. harpura (Schrank), B. naganoensis sp. nov. and B. tobiasi Khalaim. These are the first records of Barycnemis from this country. All recognized Japanese species belong to the harpura species group. An identification key to four species of Barycnemis occurring in Japan is provided. Barycnemis funiuensis Sheng, 2002 from East China is synonymised with the widely distributed Holarctic species Porizon dissimilis Gravenhorst, 1829 (syn. nov.).